(untitled) (The Journal of Theoretical Accounting Research, 2025)
This study examines the impact of governance quality on environmental degradation using panel data from 75 developing countries (1996-2020). It finds that stronger governance significantly reduces carbon dioxide emissions through enhanced accountability, disclosure credibility, and enforcement of sustainability reporting standards. The study advances sustainability accounting and governance theory by articulating accountability and disclosure assurance as mechanisms linking governance quality to environmental outcomes, with implications for both theory and practice in environmental and sustainability reporting.